The Religion and Social Movements in Indonesia: Analysis of Contemporary Problems, Their Impacts, and Their Implications A Review of the Theory of Relative Deprivacy - Kuswana, Dadang; Sumpena, Deden; Hendra Hardiyan Syah, Yoshy (Indonesian Journal of Islam and Muslim Societies, 2025)
This article examines the role of religion in contemporary social movements in Indonesia using the framework of relative deprivation theory. The phenomenon of religion-based social movements has become an integral part of the socio-political dynamics of post-Reformation Indonesia. This research presents three cases of significant religion-based social movements in Indonesia in the last decade. The cases chosen for in-depth analysis include: Action Defending Islam 2016-2017 (also known as the "212 movement"), the #2019ChangePresident Movement, and the Movement to reject the 2020 Job Creation Omnibus Law. This study examines how perceptions of injustice and socio-economic inequality trigger mass mobilization based on religious identity. This research adopts a qualitative research method with a multiple case study design. Through critical analysis of three recent cases of social movements, this research reveals the complexity of the interaction between religious, economic and political factors in shaping collective action. The findings show that, while relative deprivation plays a significant role in motivating participation in religious social movements, contextual factors such as political opportunity structures and organizational resources also play an important role. The theoretical and practical implications of these findings are discussed in the context of efforts to build social cohesion and conflict management in a diverse Indonesia